Water adsorption properties of silica gel and hydroxyethyl cellulose composite coatings - Lucas Lovis; Andrew Maddocks; Priscilla Tremain; Behdad Moghtaderi (Results in Materials)
Water scarcity is an increasingly significant global issue. Desiccant coated heat exchangers are a potential adsorption reactor for atmospheric water generation, which can alleviate water scarcity through the subsequent adsorption, desorption, and condensation of ambient humidity. Microporous and mesoporous silica gels are common and inexpensive desiccants that demonstrate moderate adsorption and desorption rates, and hence are suitable for multicyclic atmospheric water generation. To accurately model the behaviour of silica gel based desiccant coated heat exchanger-atmospheric water generation systems, the kinetic and equilibrium properties of silica gel were measured for varying coating thicknesses, hydroxyethyl cellulose binder concentrations, temperatures, and relative humidity conditions using thermogravimetric analysis. Additionally, the particle size, pore textural properties, and density of the samples were measured using scanning electron microscopy, nitrogen adsorption, and pycnometry respectively. The average particle size within the coatings increased with increasing hydroxyethyl cellulose concentration. The equilibrium uptake was lower for the coating samples compared to the powder sample and was not strongly dependant on the adsorption temperature. The kinetic constants and maximum ideal specific water production were inversely related to the coating thickness and were not strongly dependant on the hydroxyethyl cellulose concentration. The adsorption order and kinetic constant varied depending on whether monolayer adsorption, multilayer adsorption, pore filling, or capillary condensation were occurring. The effect of the change in adsorption mechanism on the kinetic constant was less significant for thicker layers and lower adsorption temperatures. The maximum ideal specific water production for the coating samples within the set of measured conditions was 57 L kg−1 day−1.